Current and future applications of corneal cross-linking. Issue 3 (May 2015) - Khandelwal, Sumitra S.; Randleman, J. Bradley
Abstract : Purpose of review: To review current concepts and future directions of corneal cross-linking (CXL) as a treatment for keratoconus, ectasia after refractive surgery and infectious keratitis. Recent findings: Several important laboratory and clinical studies have established the safety and success of corneal cross-linking for the treatment of keratoconus and other corneal ectasias. Recently, additional studies have analyzed new directions and controversies in corneal cross-linking, exploring new indications, comparing new techniques and analyzing results of new protocols. Summary: The results of bench and clinical research are providing the foundation to allow for protocol modifications of the standard cross-linking protocols and expansion of cross-linking concepts for techniques such as accelerated cross-linking, epithelium-sparing protocols and measurement of progression and success.